Fuzzy Techniques in Visual Performance and Illumination Applications - Alhamad, Issah (2020)
A thesis submitted in fulfilment of the requirements for the degree of DOCTOR OF PHILOSOPHY in Architecture and Sustainable Built environment (ASBE) At The British University in Dubai Supervisor: Prof. Riad Saraiji August 2020